Accumulation Assessment of Mo4+, Pb++, and Cu++ in the Acidic Water of Copper Mines with Lemna minor and Lemna gibba - Konakci, Nevin (Mdpi, 2024)
Pollutants accumulate in aquatic habitats due to mining activities. The duckweed family includes water plants such as Lemna gibba and Lemna minor, which are tiny, delicate, free-floating aquatic plants. L. minor and L. gibba were used in this study to examine the accumulation capacities of Mo4+, Pb++, and Cu++ in acidic fluids from copper mining. Two reactors were assigned to L. gibba and L. minor, respectively. These plants and the reactor water were gathered daily for 8 days. Acid mine water pH, temperature, and electric conductivity were also tested daily. L. gibba and L. minor were cleaned, dehydrated, and burned in a drying oven for a whole day at 300 degrees C. ICP-MS (inductively coupled plasma mass spectroscopy) was used to determine the Mo4+, Pb++, and Cu++ content of the plant and water samples. The Mo, Pb, and Cu concentrations in the copper mining acidic fluids were 30 +/- 4, 260 +/- 12, and 15,535 +/- 322 mu g L-1, respectively. Regarding Mo, Pb, and Cu extraction from copper mining acidic fluids, L. gibba and L. minor performed more efficiently than control samples, gathering 29 and 177 times more Mo, 30 and 109 times more Pb, and 495 and 1150 times more Cu, respectively. Considering these findings, L. gibba and L. minor are good plants for rehabilitating polluted waters and can efficiently remove Mo, Pb, and Cu from acid mine fluids.
Keywords: acid mine waters; heavy metals; accumulation; Lemna gibba; Lemna minor; water treatment